Silicon carbide polishing solution based on phosphoric acid-sodium dihydrogen phosphate buffer solution system
By combining a phosphate-sodium dihydrogen phosphate buffer system with modified cerium oxide abrasive particles, the problems of dispersion stability and pH control in silicon carbide polishing slurry were solved, achieving a highly efficient silicon carbide polishing effect.
Patent Information
- Application Number
- CN202411185245.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-10
AI Technical Summary
Existing silicon carbide polishing slurries have shortcomings in dispersion stability and pH control, resulting in poor polishing effects and making it difficult to meet the requirements of chemical mechanical polishing.
A highly stable silicon carbide polishing slurry was formed by using a phosphate-sodium dihydrogen phosphate buffer system, through synergistic optimization of modified cerium oxide abrasive particles and phosphorus-containing heteropoly acids, utilizing phosphate-sodium dihydrogen phosphate buffer as a dispersant and pH adjuster, and combining it with potassium permanganate as an oxidant.
The dispersion performance and stability of silicon carbide polishing slurry were improved, the polishing rate was enhanced, and the long-term stability and high-efficiency polishing effect of the polishing slurry under acidic conditions were ensured.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of silicon carbide polishing liquid, and in particular relates to a high-stability silicon carbide polishing liquid based on a phosphoric acid-sodium dihydrogen phosphate buffer system. Background Art
[0002] Silicon carbide (SiC) is the most representative third-generation wide bandgap semiconductor material. It has a wide bandgap (2.3-3.3 eV), high thermal conductivity (3-4.9 W / cm·K), high critical breakdown electric field (0.8-3.0 MV / cm), low relative dielectric constant (9.7-10), high carrier saturation migration velocity (2.0 × 10 7 cm / s), high temperature resistance (up to 1000 ℃) and radiation resistance. However, due to the high hardness of SiC single crystal materials and the fact that the compression strength is higher than its bending strength, the material is relatively brittle and chemically inert, resulting in poor thinning efficiency of SiC substrates. It can be seen that the preparation of efficient and stable silicon carbide polishing liquid has very important scientific significance and market application prospects. At present, CMP has been widely used in surface polishing and planarization in the semiconductor industry. It is considered to be the only effective processing method to achieve global planarization and ultra-smooth, damage-free nanoscale surfaces of SiC wafers. The commonly used polishing liquid generally includes abrasive particles, oxidants, pH regulators, and various additives, with the balance being water. In order to improve the thinning efficiency of silicon carbide, high-strength materials such as aluminum oxide (Mohs hardness of 9.0) and nanodiamond (Mohs hardness of 10) are usually used. While improving the thinning efficiency, it is also very easy to cause scratches on the surface of silicon carbide. Although the polishing liquid containing cerium oxide (Mohs hardness of 7-8) can improve surface scratches, in the aqueous medium, due to the high surface energy of CeO2, particles are very likely to agglomerate and settle quickly, resulting in instability of the polishing liquid, thereby affecting the final polishing effect.
[0003] In addition, potassium permanganate is preferred as an oxidant in the polishing solution due to its strong oxidizing ability. However, potassium permanganate consumes H + This causes the pH of the solution system to increase, affecting the dispersion stability of the polishing liquid system, causing abrasive particles to agglomerate and thus affecting the polishing effect. Therefore, it is critical to develop a polishing liquid with good dispersion stability and buffering capacity for the pH of the system.
[0004] The study found that using inorganic acid as a pH regulator and dispersant can obtain a relatively stable polishing solution, but the stability time in the CeO2 polishing solution is short, and agglomeration and sedimentation will still occur. The dispersion performance of the CeO2 polishing solution needs to be further improved, and the polishing rate for silicon carbide materials is low, which cannot meet the requirements of chemical mechanical polishing.
[0005] In view of the poor dispersion stability and pH stability of the cerium oxide polishing liquid in the prior art during the mechanical polishing of silicon carbide, the present invention adopts a phosphoric acid-sodium dihydrogen phosphate buffer system, and through the synergistic optimization of modified cerium oxide abrasives and phosphorus-containing heteropolyacids, it is possible to ensure that the pH value of the system remains basically unchanged while maintaining high efficiency and stability during the silicon carbide polishing process while maintaining dispersion stability. Summary of the invention The technical problem to be solved by the present invention is to provide a high-stability silicon carbide polishing liquid based on a phosphoric acid-sodium dihydrogen phosphate buffer system in view of the deficiencies in the current technology. The polishing liquid uses a phosphoric acid-sodium dihydrogen phosphate buffer solution as a dispersant and a pH regulator of the polishing liquid, and the pH value of the system is controlled to be 2.0-6.0; in addition, surface-modified cerium oxide is used as an abrasive, and a phosphorus heteropoly acid is used as a bridging bond to increase the inherent dispersion stability of cerium oxide, so that phosphate ions are adsorbed on the surface of cerium oxide, and the repulsive force between particles is increased through the double electric layer effect, and the tendency of particles to agglomerate with each other is weakened, thereby improving its dispersion performance. The dispersion performance, polishing rate and stability of the polishing liquid of the present invention are significantly improved, and the quality and performance of the silicon carbide polishing liquid are greatly improved.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A high-stability silicon carbide polishing liquid based on a phosphoric acid-sodium dihydrogen phosphate buffer system, the polishing liquid comprising the following components: 0.05%-10% modified cerium oxide; 0.05%-0.5% phosphoric acid; 0.1%-1.5% sodium dihydrogen phosphate; 0.05%-5% phosphorus heteropoly acid; 1%-10% oxidant, the balance being water, with a pH value of 2.0-6.0, preferably 2.0-4.0, and more preferably 2.0-3.0.
[0007] The particle size of the modified cerium oxide polishing liquid is 100-1000 nm.
[0008] The phosphoric acid-sodium dihydrogen phosphate buffer serves as both a system dispersant and a pH regulator.
[0009] The modified cerium oxide abrasive preparation method comprises the following steps: adding 6-{2-[2-(2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)triethoxysilane MEEETES to an aqueous solution of ethylene glycol under an inert atmosphere, adding Ce(NO3)3·6H2O under heating and reflux, adding ammonia water to induce ethylene glycol-assisted precipitation after the mixture is completely dissolved, and filtering, washing and drying to obtain the modified cerium oxide.
[0010] The unmodified cerium oxide is prepared without adding MEEETES, and the other steps are consistent with the preparation method of the modified cerium oxide abrasive.
[0011] The phosphorus-containing heteropoly acid is one or more combinations of phosphotungstic heteropoly acid, phosphomolybdic heteropoly acid, and phosphotungsticmolybdic heteropoly acid, and more preferably is phosphomolybdic heteropoly acid.
[0012] The oxidant includes one or more combinations of hydrogen peroxide, potassium hypochlorite, sodium hypochlorite, perchloric acid, potassium permanganate, periodic acid, potassium periodate, sodium periodate, potassium persulfate, ammonium persulfate, sodium persulfate, etc., and the more preferred oxidant is potassium permanganate.
[0013] The polishing liquid preparation method comprises the following steps: firstly, adding a certain amount of deionized water to the modified cerium oxide abrasive, adding phosphoric acid-sodium dihydrogen phosphate buffer after stirring, so that the solution reaches the target pH value (the pH value is 2.0-6.0, preferably 2.0-4.0, and more preferably 2.0-3.0); finally, adding phosphorus-containing heteropoly acid and oxidant according to the target concentration, and then adding deionized water to make up the balance, and continuing to stir.
[0014] The concentration of the modified cerium oxide polishing liquid is 0.05 wt%~10.0 wt%.
[0015] The phosphate-sodium dihydrogen phosphate buffer is prepared from phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphate-sodium dihydrogen phosphate buffer, the concentration of phosphoric acid is 0.05 mol / L~0.5 mol / L, and the concentration of sodium dihydrogen phosphate is 0.1 mol / L~1.5 mol / L.
[0016] The volume ratio of phosphoric acid-sodium dihydrogen phosphate buffer solution to polishing liquid is 1:500~1:1000.
[0017] The high-stability silicon carbide polishing liquid based on the phosphoric acid-sodium dihydrogen phosphate buffer system is applied to the polishing process of silicon carbide in integrated circuits.
[0018] The polishing liquid of the invention has a very high removal rate for the Si surface of the SiC single crystal, 0.7-6 μm / h for the Si surface, and the roughness Ra of 10×10 μm detected by atomic force microscope is less than 0.1 nm.
[0019] The average particle size and Zeta potential of the modified cerium oxide nanoparticles are measured by a laser nanoparticle size analyzer, wherein the particle size of 50% cumulative volume (D50) is preferably 0.12 μm~0.58 μm, and the best is 0.12 μm; the Zeta potential is preferably 19.1 mV~51.3 mV, and the best is 51.3 mV.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The phosphoric acid-sodium dihydrogen phosphate buffer of the present invention acts as a pH regulator and a dispersant at the same time. The H generated by the ionization of phosphoric acid+ The ions adjust the system to acidity, and the H2PO-4 and HPO2-4 buffer pairs keep the pH of the system stable.
[0021] 2. Use high molecular weight siloxane to in-situ coat cerium oxide nanoparticles, introduce organic siloxane on the surface of cerium oxide nanoparticles and coordinate polymerization with the multi-hydroxyl groups on the surface of cerium oxide. The siloxane-coated cerium oxide nanoparticles can reduce the high surface energy of cerium oxide and increase the apparent hydrophilicity of cerium oxide nanoparticles.
[0022] 3. Secondly, the introduction of phosphomolybdic heteropoly acid as a bridging bond allows the modified cerium oxide to be bridged with the phosphate ions through hydrogen bonds. The double electrical layer effect increases the mutual repulsion between the nanoparticles, and the tendency of the particles to agglomerate with each other is weakened. This is also the reason why the cerium oxide nanoparticles have excellent stability.
[0023] 4. Phosphoric acid-sodium dihydrogen phosphate buffer solution can avoid the damage caused by the use of volatile acids such as concentrated acetic acid, concentrated nitric acid, concentrated hydrochloric acid and hydrofluoric acid, and is suitable for long-term storage at room temperature without deterioration.
[0024] The silicon carbide substrate used in the following experiments is a 6-inch conductive silicon carbide substrate. Unless otherwise specified, the following SiC removal rates are obtained on a semi-insulating silicon carbide substrate with the Si surface.
[0025] The machine model used in the polishing experiment is the FD-4603X surface grinder of Shenzhen Fangda Grinding Technology Co., Ltd., the polishing pad is IC1000, the polishing disc diameter is 0.5 m, the polishing pressure is 4-6 psi, the polishing disc speed is 55 rpm, the polishing head speed is 50rpm, the polishing liquid flow rate is 60 mL / min or 80 mL / min, and the polishing time is 20 minutes to 40 minutes. The polishing experiment was carried out at room temperature. After polishing, the silicon carbide substrate was ultrasonically cleaned with deionized water and ethanol and then dried with nitrogen. The removal rate of silicon carbide (μm / h) was obtained by the weight change and polishing time of the silicon carbide substrate before and after polishing. The average particle size and Zeta potential in this application are measured by a laser nanoparticle size analyzer, model Nicomp 380DLS, American PSS. (The concentration percentages in this application, unless otherwise specified, are all mass percentages) DETAILED DESCRIPTION In the present invention, modified cerium dioxide abrasive: surface modified cerium oxide is synthesized by ammonia-induced ethylene glycol (EG)-assisted precipitation method. First, 7.8 mL (0.12 mol) of EG is added to 92.2 mL of deionized water in a three-necked flask as a reactor, 0.4 mL of 6-{2-[2-(2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)triethoxysilane MEEETES (20 mM) is added to the mixed solution under an inert atmosphere, and the mixture is stirred at a constant magnetic force of 200 rmp in a water bath reflux condenser system at 50°C. Then, Ce(NO3)3·6H2O (5.16 g, 0.012 mol) is added to the EG / H2O solution and completely dissolved, 5 mL of ammonia (NH4OH) is added to the solution, and the pH value is adjusted to 9.0. The solution was kept under constant stirring at 500 rpm and allowed to react until the solution color changed to light yellow, then stirring was stopped and the entire reaction volume was vacuum filtered using a Buchner funnel. The filtered nanomaterials were washed alternately with ethanol and deionized water and dried in a fume hood overnight.
[0026] The unmodified cerium dioxide abrasive was prepared without adding MEEETES, and the other steps were consistent with the preparation steps of the modified cerium oxide mentioned above.
[0027] Example 1 Prepare 500 g of unmodified cerium oxide polishing liquid, take 25 g of 5% unmodified cerium dioxide abrasive, add 300 g of deionized water, stir evenly, add a certain amount of phosphoric acid, adjust the polishing liquid to pH = 3, and finally make up the balance with deionized water and continue to stir evenly. Test its average particle size (D50) and Zeta potential at 0, 1, 3, 5, and 7 days.
[0028] Table 1 Dispersion stability of unmodified cerium oxide polishing liquid in phosphoric acid Days Parameters 0 1 3 5 7 Average particle size (D50) 365.3 370.5 435.4 467.3 585.6 Zeta (mV) 41.37 40.24 35.73 28.59 19.05 It can be concluded that, with phosphoric acid as the dispersant, the average particle size (D50) of the unmodified cerium oxide abrasive increased from 365.3 nm to 585.6 nm after one week. The average particle size showed an overall increasing trend. For the Zeta potential, on the 0th day, the Zeta potential of the unmodified cerium oxide polishing liquid was 41.37 mV; on the 7th day, the Zeta potential of the cerium oxide abrasive was 19.05 mV. The Zeta potential was lower than 30 mV, indicating that the dispersion performance of the polishing liquid was poor at this time.
[0029] Example 2 Prepare 500 g of unmodified cerium oxide polishing liquid, take 25 g of unmodified cerium dioxide abrasive with a mass fraction of 5%, add 300 g of deionized water to it, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), adjust the polishing liquid to pH=3, and finally make up the balance with deionized water, and continue to stir evenly. Test its average particle size (D50) and Zeta potential at 0, 1, 3, 5, and 7 days.
[0030] Table 2 Dispersion stability of unmodified cerium oxide polishing liquid after phosphoric acid-sodium dihydrogen phosphate
[0031] It can be concluded that, with phosphoric acid-sodium dihydrogen phosphate as the dispersant, the average particle size (D50) of the unmodified cerium oxide abrasive increased from 289.4 nm to 455.2 nm after one week. The average particle size showed an overall increasing trend. For the Zeta potential, on the 0th day, the Zeta potential of the unmodified cerium oxide polishing liquid was 43.24 mV; on the 7th day, the Zeta potential of the cerium oxide abrasive was 29.87 mV. The Zeta potential was greater than 30 mV on days 1-5, and was less than 30 mV on the seventh day, indicating that the dispersion performance of the polishing liquid after dispersion with phosphoric acid-sodium dihydrogen phosphate was slightly better than that of phosphoric acid dispersion, but the long-term dispersion effect was still poor.
[0032] Example 3 The stability of the modified cerium oxide polishing liquid dispersed by phosphoric acid-sodium dihydrogen phosphate is shown in Table 3: Prepare 500 g of modified cerium oxide polishing liquid, take 25 g of modified cerium dioxide abrasive with a mass fraction of 5%, add 300 g of deionized water to it, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), adjust the polishing liquid to pH=3, and finally make up the balance with deionized water, and continue to stir evenly. Test its average particle size (D50) and Zeta potential at 0, 1, 3, 5, and 7 days.
[0033] Table 3 Dispersion stability of modified cerium oxide polishing liquid after phosphoric acid-sodium dihydrogen phosphate
[0034] It can be concluded that the average particle size (D50) of cerium oxide abrasive increases from 153.3 nm to 188.6 nm when phosphoric acid-sodium dihydrogen phosphate is used as dispersant and modified cerium oxide is used as abrasive. The average particle size shows an overall increasing trend. For Zeta potential, on the 0th day, the Zeta potential of the modified cerium oxide polishing liquid is 47.55 mV; on the 7th day, the Zeta potential is 34.58 mV and still remains greater than 30 mV, indicating that the modified cerium oxide abrasive and the polishing liquid after dispersion by phosphoric acid-sodium dihydrogen phosphate still maintain good dispersion performance within one week.
[0035] Example 4 The stability of modified cerium oxide and phosphomolybdic heteropoly acid dispersed in phosphoric acid-sodium dihydrogen phosphate is shown in Table 4: Prepare 500 g of modified cerium oxide polishing liquid, take 25 g of 5% modified cerium dioxide abrasive, 10 g of 2% phosphomolybdic heteropoly acid, add 300 g of deionized water, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration of 85 wt%) and sodium dihydrogen phosphate crystals; in phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), adjust the polishing liquid to pH=3, and finally make up the balance with deionized water, and continue to stir evenly. Test its average particle size (D50) and Zeta potential at 0, 1, 3, 5, and 7 days.
[0036] Table 4 Stability of modified cerium oxide and phosphomolybdic heteropoly acid dispersed in phosphoric acid-sodium dihydrogen phosphate
[0037] It is concluded that the average particle size (D50) of the modified cerium oxide abrasive only increased from 120.6 nm to 132.4 nm when phosphoric acid-sodium dihydrogen phosphate was used as a dispersant, modified cerium oxide was used as an abrasive, and phosphomolybdic heteropoly acid was used as an additive. For the Zeta potential, the Zeta potential of the modified cerium oxide polishing liquid was 51.3 mV on the 0th day; on the 7th day, the Zeta potential was 45.2 mV and still remained greater than 45 mV, indicating that the modified cerium oxide abrasive and the phosphorus-containing heteropoly acid as an additive, through the synergistic effects of phosphoric acid-sodium dihydrogen phosphate dispersion, the polishing liquid can still maintain excellent dispersion performance within a week.
[0038] In this embodiment, experiments were conducted using phosphomolybdic heteropoly acid as an additive, and the experiments found that phosphotungstic heteropoly acid and phosphotungstomolybdic heteropoly acid also had similar technical effects.
[0039] Example 5 Polishing properties of unmodified cerium oxide after dispersion in phosphoric acid Prepare 1000 g of cerium oxide polishing liquid, take 50 g of unmodified cerium oxide abrasive with a mass fraction of 5%, add 600 g of deionized water, stir evenly, add a certain amount of phosphoric acid and 5% concentration of potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the remainder with deionized water and continue to stir evenly.
[0040] A silicon carbide wafer (purity of 99.99%) with a diameter of 150 mm and a thickness of 353 μm was polished, and the removal rate MRR of the polishing liquid on the silicon carbide wafer was measured to be 0.685 μm / h; the roughness Ra was 0.15 nm.
[0041] Example 6 Polishing properties of unmodified cerium oxide after dispersion with phosphoric acid-sodium dihydrogen phosphate Prepare 1000 g of cerium oxide polishing liquid, take 50 g of unmodified cerium oxide abrasive with a mass fraction of 5%, add 600 g of deionized water to it, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), and 5% potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the remainder with deionized water and continue to stir evenly.
[0042] A silicon carbide wafer (purity of 99.99%) with a diameter of 150 mm and a thickness of 353 μm was polished, and the removal rate MRR of the polishing liquid on the silicon carbide wafer was measured to be 1.25 μm / h; the roughness Ra was 0.11 nm.
[0043] Example 7 Polishing properties of modified cerium oxide dispersed in phosphoric acid-sodium dihydrogen phosphate Prepare 1000 g of cerium oxide polishing liquid, take 50 g of modified cerium oxide abrasive with a mass fraction of 5%, add 600 g of deionized water to it, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), and 5% concentration of potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the remainder with deionized water and continue to stir evenly.
[0044] A silicon carbide wafer (purity of 99.99%) with a diameter of 150 mm and a thickness of 353 μm was polished, and the removal rate MRR of the polishing liquid on the silicon carbide wafer was measured to be 4.36 μm / h; the roughness Ra was 0.11 nm.
[0045] Example 8 Polishing properties of modified cerium oxide and phosphomolybdic heteropoly acid dispersed in phosphoric acid-sodium dihydrogen phosphate Prepare 1000 g of cerium oxide polishing liquid, take 50 g of modified cerium oxide abrasive with a mass fraction of 5%, 10 g of phosphomolybdic heteropoly acid with a mass fraction of 2%, add 600 g of deionized water, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), and 5% potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the remainder with deionized water, and continue to stir evenly.
[0046] A silicon carbide wafer (purity of 99.99%) with a diameter of 150 mm and a thickness of 353 μm was polished, and the removal rate MRR of the polishing liquid on the silicon carbide wafer was measured to be 6.12 μm / h; the roughness Ra was 0.06 nm.
[0047] The polishing performance of the product obtained in Example 8 under different pH conditions is shown in Table 5: Prepare 1000 g of cerium oxide polishing liquid, take 50 g of modified cerium oxide abrasive with a mass fraction of 5%, 10 g of phosphomolybdic heteropoly acid with a mass fraction of 2%, add 600 g of deionized water, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration of 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), and 5% potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the balance with deionized water, and continue to stir evenly. The difference is that the pH of the polishing liquid is adjusted to 2.0, 4.0, 5.0, and 6.0, respectively, and the polishing performance is tested.
[0048] Table 5 Polishing performance of Example 8 under different pH conditions
[0049] As shown in Table 5, as the pH value increases from 2.0 to 6.0, the removal rate of SiC increases first and then decreases, but all of them are excellent. In particular, at pH = 3.0, the removal rate of SiC is the largest, which is 6.12 μm / h and the roughness Ra = 0.06 nm.
[0050] The polishing performance of the product obtained in Example 8 at different KMnO4 concentrations is shown in Table 6: Preparation of 1000 g cerium oxide polishing liquid Take 50 g of 5% modified cerium oxide abrasive and 10 g of 2% phosphomolybdic heteropoly acid, add 600 g of deionized water, stir evenly, add a certain amount of phosphoric acid-sodium dihydrogen phosphate (phosphoric acid (concentration is 85 wt%) and sodium dihydrogen phosphate crystals; in the phosphoric acid-sodium dihydrogen phosphate buffer, the phosphoric acid concentration is 0.2 mol / L, and the sodium dihydrogen phosphate concentration is 1.0 mol / L), and the preferred 5% concentration of potassium permanganate solution, adjust the pH of the polishing liquid to 3.0, and finally make up the balance with deionized water, and continue to stir evenly. The difference is that the concentration of KMnO4 is 1%, 2%, 3%, and 4%, respectively, and the polishing performance is tested.
[0051] Table 6 Polishing performance of Example 8 under different pH conditions
[0052] By comparing Examples 1 and 2, it is concluded that potassium permanganate acts as an oxidant in SiC polishing, accompanied by thinning under mechanical action. When the pH is in the range of 2-6, the oxidizing ability of potassium permanganate increases first and then decreases, and both perform excellently. The oxidizing ability of potassium permanganate also increases with the increase of its concentration, but too high a concentration will exceed the solubility and precipitate, so the preferred maximum concentration is 5%.
[0053] Due to the high hardness of silicon carbide, it is impossible to oxidize the material into a softer intermediate product by adding a single oxidant and then remove it. Abrasives, dispersants, additives and pH values are key factors affecting the polishing rate of silicon carbide. Therefore, the present invention obtains a dispersed and stable cerium dioxide polishing liquid by adding phosphoric acid-sodium dihydrogen phosphate buffer solution as a pH regulator and dispersant. During the polishing process, the pH of the system is kept stable, ensuring the optimal oxidizing property of the oxidant potassium permanganate, so that the oxidant and the silicon carbide surface chemical reaction are more sufficient, thereby obtaining a high silicon carbide polishing rate.
[0054] Phosphoric acid-sodium dihydrogen phosphate buffer solution is added to the cerium oxide polishing liquid. Under acidic conditions, the ionized phosphate ions will be adsorbed on the surface of the cerium oxide particles to increase the repulsive force between the cerium oxide nanoparticles through the double electric layer effect, thereby improving its dispersion performance. In addition, the cerium oxide nanoparticles are in situ coated with high molecular weight siloxane, and organic siloxane is introduced on the surface of the cerium oxide nanoparticles to coordinate polymerization with the multi-hydroxyl group on the surface of the cerium oxide. The siloxane-coated cerium oxide nanoparticles can reduce the high surface energy of cerium oxide and increase the apparent hydrophilicity of the cerium oxide nanoparticles. Secondly, the introduction of phosphomolybdic heteropoly acid as a bridging bond allows the modified cerium oxide to be bridged with the phosphate ions through hydrogen bonds, and the repulsive force between the nanoparticles is further increased through the double electric layer effect, and the tendency of the particles to agglomerate with each other is weakened, thereby obtaining a highly stable cerium oxide dispersion.
[0055] In summary, under the multi-step synergistic effect of in-situ encapsulation of modified cerium oxide and phosphorus-containing heteropolyacid by siloxane and phosphoric acid-sodium dihydrogen phosphate buffer solution, the Zeta of the polishing liquid is 51.3 mV and the average particle size is 120.6 nm, indicating that it has better dispersion performance and longer stability time. The optimized formula concentration can maintain the polishing efficiency of silicon carbide at 6.12 μm / h and Ra=0.06nm, reaching the industry-leading level.
[0056] It should be noted that the preferred embodiments of the present invention are described above, and that a person skilled in the art may make several improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be regarded as within the protection scope of the present invention.
Claims
1. A silicon carbide polishing liquid based on a phosphoric acid-sodium dihydrogen phosphate buffer system, characterized in that: The polishing liquid comprises the following components: modified cerium oxide abrasive grains, phosphoric acid-sodium dihydrogen phosphate buffer, phosphorus-containing heteropoly acid, oxidant and water, wherein the modified cerium oxide abrasive grains comprise 0.05% to 20% by mass; the phosphoric acid-sodium dihydrogen phosphate buffer comprises 0.15% to 2.0%; the phosphoric acid-sodium dihydrogen phosphate buffer comprises 0.05% to 5%; the phosphorus-containing heteropoly acid comprises 1% to 10%; and the balance is water.
2. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The preparation method of modified cerium oxide abrasive comprises the following steps: adding 6-{2-[2-(2-(2-methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)triethoxysilane MEEETES to an aqueous solution of ethylene glycol under an inert atmosphere, adding Ce(NO3)3·6H2O under heating reflux, adding ammonia water to induce ethylene glycol-assisted precipitation after complete dissolution, and preparing modified cerium oxide through filtering, washing and drying.
3. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The modified cerium oxide abrasive grains have a particle size of 100-1000 nm, and the purity of the modified cerium oxide is greater than or equal to 99wt%.
4. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The phosphorus-containing heteropoly acid is one or more combinations of phosphotungstic heteropoly acid, phosphomolybdic heteropoly acid, and phosphotungsticmolybdic heteropoly acid, and more preferably is phosphomolybdic heteropoly acid.
5. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The oxidant includes one or more combinations of hydrogen peroxide, potassium hypochlorite, sodium hypochlorite, perchloric acid, potassium permanganate, periodic acid, potassium periodate, sodium periodate, potassium persulfate, ammonium persulfate, sodium persulfate, etc., and the more preferred oxidant is potassium permanganate.
6. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The phosphate-sodium dihydrogen phosphate buffer is prepared from phosphoric acid and sodium dihydrogen phosphate crystals; in the phosphate-sodium dihydrogen phosphate buffer, the concentration of phosphoric acid is 0.05 mol / L-0.5 mol / L, and the concentration of sodium dihydrogen phosphate is 0.1 mol / L-1.5 mol / L.
7. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The volume ratio of the phosphoric acid-sodium dihydrogen phosphate buffer solution to the polishing liquid is 1:500~1:1000; the pH value of the polishing liquid is 2.0~6.
0.
8. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The method comprises the following steps: adding a certain amount of deionized water to the modified cerium dioxide abrasive, stirring, adding phosphoric acid-sodium dihydrogen phosphate buffer to make the solution reach a target pH value; finally, adding phosphorus-containing heteropoly acid and oxidant according to the target concentration, adding deionized water to make up the balance, and continuing to stir to prepare a polishing liquid.
9. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: The concentration of the modified cerium oxide polishing liquid is 0.05 wt%~10.0 wt%.
10. The silicon carbide polishing liquid based on phosphoric acid-sodium dihydrogen phosphate buffer system according to claim 1, characterized in that: Use of the polishing liquid according to any one of claims 1 to 9 in polishing a silicon carbide substrate by chemical mechanical polishing.